Halogenated organic compounds in water and in wastewater - Włodarczyk-Makuła, Maria; Wiśniowska, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Currently, organic halogen compounds (halogen derivatives) are often identified in water. The paper presents the problem of the presence of these newly formed compounds during water treatment processes and their occurrence in sewage. The general indicator determining the content of these compounds in aqueous solutions is the concentration of halogen derivatives of organic compounds adsorbed on activated carbon AOX, which is converted to the concentration of chlorides. The groups of derivatives of halogenated organic compounds containing chlorine and/or bromine in a molecule were characterized, and the precursors and potential for the formation of these compounds in water were described. Moreover, technological methods to prevent and remove them were described.
Keywords: organic compounds; wastewater; water; halogenated compounds; NOM; DBPs; OBPs; AOX; THM; HAN; CP; związki organiczne; ścieki; woda; HK; CH